Resilient behavior in elderly person convicted of sexual abuse, of the penitentiary and prisoner’s center INPEC of Girardot, Colombia: Systematization of the professional practice in Social Work (Emancipação, 2020)
The systematization arises as the possibility of evaluating the experience lived in the exercise of professional practice with older people who are deprived of their liberty in the penitentiary and prison INPEC of the city of Girardot, condemned for sexual abuse, and they find them selves in an intervention process oriented towards the socialization and strengthening of resilient behaviors, based on a pedagogical training strategy that explores the corporal, affective, psychosocial and cognitive dimensions of the population. The critical theoretical approach proposed by (CADENA, 1987, p .41-52) was used, in which it suggests a scheme to systematize organizational, training and promotion experiences (CIFUENTES, 1999, p. 46). The obtained results allow to strengthen the processes developed by the lines of intervention practiced by students of Social Work and applied in the penitentiary center of Girardot,guaranteeing the social acceptance of this group, excluded for their criminal behavior.
Keywords: Social intervention, Sexual abuse, Elderly person, Resilient behavior.